Downregulated microRNA-148b in circulating PBMCs in chronic myeloid leukemia patients with undetectable minimal residual disease: a possible biomarker to discontinue imatinib safely - Ohyashiki JH; Ohtsuki K; Mizoguchi I; Yoshimoto T; Katagiri S; Umezu T; Ohyashiki K (Dove Medical Press, 2014)
Junko H Ohyashiki,1 Kazushige Ohtsuki,1 Izuru Mizoguchi,2 Takayuki Yoshimoto,2 Seiichiro Katagiri,3 Tomohiro Umezu,1,4 Kazuma Ohyashiki3,4 1Department of Molecular Oncology, Institute of Medical Science, 2Department of Immunoregulation, Institute of Medical Science, 3Department of Hematology, 4Department of Molecular Science, Tokyo Medical University, Tokyo, Japan Background: A subset of patients with chronic myeloid leukemia (CML) can sustain a complete molecular response after discontinuing imatinib mesylate (IM). We focused on microRNAs (miRNAs), with the aim of finding a molecular biomarker to discriminate which patients can safely and successfully discontinue IM use. Methods: To identify miRNAs that showed altered expression in patients who had discontinued IM (STOP-IM group), we first screened miRNA expression of peripheral blood mononuclear cells by using a TaqMan miRNA array on samples from five unselected patients from the STOP-IM group, seven CML patients receiving IM (IM group), and five healthy volunteers. We then performed miRNA quantification in 49 CML patients with deep molecular response. Mann–Whitney U and chi-square tests were used to determine statistical significance for comparisons between the control (healthy volunteers) and test groups (STOP-IM and IM groups). Multiple groups were compared by one-way analysis of variance. Results: Downregulation of miR-148b was noted in patients in the STOP-IM group and in a subset of the IM group. We then subdivided the IM patients into two groups: one with downregulated miR-148b expression (IM-1; less than the cut-off value) and the other without downregulated miR-148b expression (IM-2; greater than the cut-off value). The number of patients who had a sustained stable molecular response was significantly lower in IM-2 group. This group also had a significantly lower percentage of natural killer cells. Conclusion: Downregulated miR-148 may contribute to immune surveillance in STOP-IM patients and may therefore have potential as additive information in managing CML patients undergoing treatment with IM. Keywords: chronic myeloid leukemia, imatinib mesylate, discontinuation, miR-148b